2021
DOI: 10.1007/s11845-021-02743-8
|View full text |Cite
|
Sign up to set email alerts
|

Thiol level and total oxidant/antioxidant status in patients with COVID-19 infection

Abstract: Background Accumulating evidence suggests that oxidative stress is closely related to the pathogenesis and severity of COVID-19 infection. Here, we attempted to compare thiol, total oxidant status (TOS), total antioxidant status (TAS), and oxidative stress index (OSI) levels between COVID-19 patients who need and do not need intensive care unit (ICU) support, and determine whether these markers could be used as predictors of ICU admission. Methods We recruited 86 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
6
22
2
Order By: Relevance
“…A wide range of biomolecules associated with the inflammatory and immune cell response, which are used as predictors of organ failure and severity in other diseases, are also being studied in patients with COVID-19 [38] , [39] . It has been found that several inflammatory and oxidative mediators are misregulated in COVID-19 and are associated with multiorgan damage and poor disease prognosis [40] , [41] .…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of biomolecules associated with the inflammatory and immune cell response, which are used as predictors of organ failure and severity in other diseases, are also being studied in patients with COVID-19 [38] , [39] . It has been found that several inflammatory and oxidative mediators are misregulated in COVID-19 and are associated with multiorgan damage and poor disease prognosis [40] , [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chronic inflammation is associated with the production of reactive oxygen species that can promote the development of some types of cancer, insulin resistance and vascular lesions [ [77] , [78] , [79] ]. In COVID-19 patients, serum levels of glutathione and total thiol are decreased, while levels of superoxide dismutase, catalase, malondialdehyde (a marker of oxidative stress and lipoperoxidation) and the total oxidant status are increased [ 57 , [80] , [81] , [82] ]. Oxidative stress levels correlated with blood oxygen saturation levels, disease severity, prognosis, and with the virus variant that was causing the infection [ 57 , 80 , 82 , 83 ].…”
Section: Potential Indirect Mechanisms Of Sars-cov-2 Induced Dna Damage: Aberrant Inflammation Immune Response and Oxidative Damagementioning
confidence: 99%
“…In COVID-19 patients, serum levels of glutathione and total thiol are decreased, while levels of superoxide dismutase, catalase, malondialdehyde (a marker of oxidative stress and lipoperoxidation) and the total oxidant status are increased [ 57 , [80] , [81] , [82] ]. Oxidative stress levels correlated with blood oxygen saturation levels, disease severity, prognosis, and with the virus variant that was causing the infection [ 57 , 80 , 82 , 83 ]. Mechanistically, an analysis of transcriptome changes observed in different data sets from blood cells, lung biopsies or leukocytes from healthy subjects and COVID-19 patients showed that there is a significant upregulation of pro-oxidant genes, principally the myeloperoxidase and calprotectin genes [ 84 ].…”
Section: Potential Indirect Mechanisms Of Sars-cov-2 Induced Dna Damage: Aberrant Inflammation Immune Response and Oxidative Damagementioning
confidence: 99%
“…Lower levels of vitamin D, higher levels of peroxides in plasma, and higher oxidative stress index were found in severe compared to moderate COVID-19 hospitalized patients [ 73 ]. Moreover, significantly higher total oxidant status and oxidative stress index were observed in ICU compared to non-ICU patients [ 85 ]. Nevertheless, some studies found no correlation between oxidative stress markers’ levels at admission to ICU and COVID-19 outcome [ 86 ].…”
Section: Oxidative Stress and Covid-19 Severitymentioning
confidence: 99%
“…At the moment of hospitalization, levels of native thiol and total thiol were significantly lower in COVID-19 patients compared to healthy controls [ 69 , 89 ] and in severe compared to mild to moderate adults [ 88 , 89 ] and pediatric patients [ 88 ]. In hospitalized patients, thiol levels were decreasing with increasing disease severity [ 90 ], in COVID-19 patients with acute respiratory distress syndrome (ARDS) compared to those without ARDS [ 92 ], and in ICU admitted compared to non-ICU COVID-19 patients [ 85 ].…”
Section: Oxidative Stress Markers In Covid-19mentioning
confidence: 99%